A method for preparing nanocrystalline WC film by magnetron sputtering of pure WC compound target

CN118516649BActive Publication Date: 2026-10-09SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410435180.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2026-10-09
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

目前磁控溅射技术制备WC薄膜的方法主要可以分为反应式磁控溅射、非反应式磁控溅射、双靶共溅射等,其中双靶共溅射通常采用金属W靶与石墨靶共沉积WC薄膜,文章《Mechanical and tribological properties of W/WC coating with C2H2ionization-assisted deposition》使用该方法制备的WC薄膜硬度大约为18GPa左右;此外,文章《Structure and mechanical properties of reactive and non-reactive sputterdeposited WC based coatings》指出,当通入反应气体由反应式磁控溅射制备WC薄膜时,活性碳源气体的引入将影响键合,碳源气体中的碳原子更容易被电离,但可能不会完全分裂成H离子和C离子,而以C-H的形式到达基体表面,最终影响WC涂层中的非晶碳含量

Benefits of technology

[0026] (1) Existing technologies mostly employ reactive magnetron sputtering to prepare WC coatings, using combustible gases such as methane and acetylene as the reaction gases. The introduction of carbon source gases can contaminate the chamber, and incomplete cleaning will affect the quality of subsequent coating preparations and increase maintenance costs. Furthermore, carbon deposits within the chamber will affect the movement accuracy of internal mechanical components. Therefore, this invention uses a high-purity WC compound target and employs non-reactive magnetron sputtering technology to prepare nanostructured WC films with high adhesion, high hardness, and good toughness suitable for different substrates. This avoids contamination of the chamber by introducing carbon source gases and also avoids the safety hazards associated with using combustible gases and other hazardous gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118516649B_ABST
    Figure CN118516649B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing nanocrystalline WC film by magnetron sputtering of pure WC compound target, and specifically, the method is a combination of pre-ionization of argon by arc-enhanced glow discharge technology and magnetron sputtering of high-purity WC target, and a plurality of key parameters are specially controlled to achieve technology fusion, and in a higher sputtering power range, direct current magnetron sputtering technology and high-power pulse magnetron sputtering technology are respectively used to realize preparation of nanocrystalline WC film of WC 1‑x and W2C phases. The preparation method is controllable, and the nanocrystalline WC film with high hardness, high adhesion and low stress can be obtained on the surface of the cemented carbide substrate, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material surface processing, specifically to a method for preparing nanocrystalline WC thin films by magnetron sputtering of pure WC compound targets and the nanocrystalline WC thin films. Background Technology

[0002] Physical vapor deposition (PVD) for thin film preparation can be categorized into three main types: vacuum evaporation, vacuum ion plating, and sputtering. Compared to vacuum evaporation, magnetron sputtering offers several advantages: higher energy of deposited particles, resulting in denser films with better adhesion to the substrate; more effective control over the composition of alloy films; and the ability to use sputtering targets that can be almost any metal, compound, or refractory material, allowing for the preparation of films on various substrates. High-power pulsed magnetron sputtering is a rapidly developing ionization PVD technique in recent years. Its greatest advantage lies in utilizing high pulse peak power and low pulse duty cycle to generate high sputtered metal ionization rates. This technique combines the advantages of traditional magnetron sputtering (low temperature deposition, smooth surface, no particle defects) with cathode arc ion plating (high metal ionization rate, strong film-substrate adhesion, and dense coating). Furthermore, the ion beam does not contain large particles, allowing for excellent film-substrate adhesion while controlling the coating microstructure. It offers significant technical advantages in reducing coating internal stress and improving coating density and uniformity.

[0003] Arc-enhanced glow discharge (AGF) technology generates high-density plasma through arc discharge. This high-density electron flow, drawn into the chamber by the anode rod, ionizes the argon gas within, producing a high density of argon ions and significantly improving the ionization rate. Due to the high argon ion density, the substrate does not require a negative voltage of 800–1000V; a negative voltage below 200V is sufficient to achieve good surface cleaning. Compared to traditional ion etching cleaning, AGF effectively avoids substrate surface damage and significantly reduces surface impurities.

[0004] Tungsten carbide (WC) is a transition metal carbide with excellent comprehensive properties, such as high hardness, high elastic modulus, corrosion resistance, high temperature resistance and low coefficient of friction. It is widely used in the field of surface wear-resistant and friction-reducing protection of key components of molds and equipment. Currently, methods for preparing WC thin films using magnetron sputtering can be mainly divided into reactive magnetron sputtering, non-reactive magnetron sputtering, and dual-target co-sputtering. Dual-target co-sputtering typically involves co-depositing WC films using a metal W target and a graphite target. The article "Mechanical and tribological properties of W / WC coating with C2H2ionization-assisted deposition" describes WC films prepared using this method with a hardness of approximately 18 GPa. Furthermore, the article "Structure and mechanical properties of reactive and non-reactive sputter-deposited WC based coatings" points out that when reactive gases are introduced for WC film preparation via reactive magnetron sputtering, the introduction of active carbon source gas affects bonding. Carbon atoms in the carbon source gas are more easily ionized, but may not completely split into H and C ions, instead reaching the substrate surface as CH ions, ultimately affecting the amorphous carbon content in the WC coating. Therefore, both existing methods are unfavorable for high-hardness WC film deposition and exhibit poor adhesion. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing nanocrystalline WC thin films by magnetron sputtering of pure WC compound targets. This preparation method is controllable and can obtain nanocrystalline WC thin films with high hardness, high adhesion, and low stress on the surface of cemented carbide substrates, which has good application prospects.

[0006] This invention employs a combination of arc-enhanced glow discharge technology for pre-ionizing argon gas and magnetron sputtering of a high-purity WC target. By carefully controlling several key preparation parameters, the technology achieves fusion, enabling the use of DC magnetron sputtering and high-power pulsed magnetron sputtering techniques to achieve WC targets within a higher sputtering power range. 1-x Controllable preparation of nanocrystalline WC thin films with W2C phase enables high hardness, high adhesion, and low stress deposition of nanocrystalline WC thin films on the surface of cemented carbide substrates.

[0007] This invention discloses a method for preparing nanocrystalline WC thin films using a magnetron sputtering pure WC compound target. The method is based on a combination of arc-enhanced glow discharge pre-ionized argon gas and a magnetron sputtering high-purity WC target, and includes the following steps:

[0008] 1) Substrate surface pretreatment: After grinding, polishing, cleaning and drying the surface of the substrate to be coated, it is fixed on a planetary table that can rotate in three dimensions and sent into the chamber.

[0009] 2) Chamber vacuum heating: The chamber is evacuated to a vacuum and subjected to multi-stage vacuum heating to remove volatile impurities from the chamber and substrate surface. The heating temperature is set to 550-600℃.

[0010] 3) Ion etching of substrate surface: High-purity argon gas is continuously introduced into the chamber to maintain a constant temperature and pressure in the chamber. A negative bias is applied to the substrate, and arc-enhanced glow discharge technology is used to perform ion cleaning and etching on the substrate to remove the oxide scale and loose layer on the substrate surface.

[0011] 4) Preparation of WC thin film: High-purity argon gas is continuously introduced into the chamber, a high-purity WC compound target is used, the temperature of the infrared heating tube in the chamber is kept constant, a negative bias voltage is applied to the substrate, and the substrate is treated with magnetron sputtering technology to deposit a nanocrystalline WC thin film.

[0012] 5) Cooling and sampling: After the film deposition is completed, the substrate is cooled to obtain a nanocrystalline WC film on the substrate surface.

[0013] An external circulating water cooling device can be used. The cooling water temperature is set to 15-20℃ and the warm water temperature is set to 35-40℃. Once the chamber is cooled to below 70℃ under vacuum, the substrate can be removed to obtain a nanocrystalline WC film on the surface of the metal substrate.

[0014] Furthermore, the surface roughness Ra value of the substrate in step 1) is below 0.4 μm; ultrasonic cleaning is performed by ultrasonically cleaning the substrate with anhydrous ethanol for 10-20 minutes, and then drying it with hot air.

[0015] Furthermore, the chamber is constructed by covering the entire rear wall with infrared electric heating tubes. The temperature within the chamber is measured by thermocouples positioned at three locations on the front side of the chamber: upper, middle, and lower. This allows for controlled and uniform heating of the substrate material within the chamber, ensuring the stability of sample quality on small-scale industrial production equipment.

[0016] Furthermore, in step 2), the chamber is first evacuated to a vacuum level of 4 × 10⁻⁶. -5 Below mbar, the first heating is performed, for example, setting the infrared heating tube temperature to 600℃ and the heating time to 30 minutes; then the chamber vacuum is evacuated to 4×10 -5 Below mbar, a second heating is performed. The second heating temperature is lower than the first heating temperature. For example, the infrared heating tube temperature is set to 550℃ and the heating time is set to 30 minutes. Finally, the chamber is evacuated to a vacuum degree of 4×10⁻⁶ mbar. -5 Below mbar.

[0017] Furthermore, in step 3), the infrared heating tube is heated to a temperature of 500-600°C, and the argon gas pressure is 0.2-2.0 Pa. For example, the argon gas flow rate is controlled by the gas pressure to be 160 sccm. Arc-enhanced glow discharge technology is used to allow the high-density electron flow to collide with the introduced argon gas. The ion cleaning and etching time for the substrate is 30-60 min.

[0018] Temperature and gas pressure during ion etching cleaning affect the mean free path of ionized argon ions, thus affecting the quality of ion cleaning. Our research team has found through numerous experiments that within the above parameter range, the mean free path of gas molecules and ionized argon ions is moderate, which ensures both the number of ions reaching the substrate surface per unit time and the energy of the ions reaching the substrate surface, thereby ensuring both the efficiency and quality of ion cleaning.

[0019] Furthermore, in step 3), during the ion cleaning and etching process on the substrate surface, the cathode arc target that serves as the electron source is a Ti target with a purity of over 99% and a target current of 70–90 A; the planetary carrier on which the substrate is placed is connected to the negative terminal of a pulse power supply with a negative bias voltage of -50 to -200 V, using a bipolar pulse with a frequency of 15–20 kHz and a duty cycle of 60–80%.

[0020] Furthermore, in step 4), the sputtering target is a rectangular WC compound target with a purity of 99.9% and a size of 456mm × 81mm × 10mm.

[0021] In one implementation, in step 4), when DC magnetron sputtering technology is used, the average sputtering power of the target material is 3kW to 4kW; the planetary carrier on which the substrate is placed is connected to the negative terminal of the power supply, the negative bias voltage is -90 to -110V, and the thin film deposition time is 100 to 120min.

[0022] As another implementation, in step 4), when high-power pulsed magnetron sputtering technology is used, the average sputtering power of the target is 3kW, the pulse duty cycle is 0.5% to 5%, the planetary carrier for placing the substrate is connected to the negative terminal of the power supply, the negative bias voltage is -90 to -110V, and the thin film deposition time is 160 to 180min.

[0023] This invention also provides a nanocrystalline WC thin film on a metal substrate, prepared using the above-described method. A nanocrystalline WC thin film with high hardness, high adhesion, and low stress is obtained on the surface of a cemented carbide substrate. Specifically, WC is prepared... 1-x Nanocrystalline WC thin films with W2C phase.

[0024] The present invention employs a combination of arc-enhanced glow discharge technology with pre-ionized argon gas and magnetron sputtering of a high-purity WC target. By precisely controlling multiple preparation parameters, under specially set conditions such as multi-stage vacuum heating, temperature and pressure during ion etching and cleaning, substrate negative bias, chamber pressure, and sputtering target power, nanocrystalline WC thin films with a hardness of over 32 GPa can be controlled to be prepared on the surface of cemented carbide.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) Existing technologies mostly employ reactive magnetron sputtering to prepare WC coatings, using combustible gases such as methane and acetylene as the reaction gases. The introduction of carbon source gases can contaminate the chamber, and incomplete cleaning will affect the quality of subsequent coating preparations and increase maintenance costs. Furthermore, carbon deposits within the chamber will affect the movement accuracy of internal mechanical components. Therefore, this invention uses a high-purity WC compound target and employs non-reactive magnetron sputtering technology to prepare nanostructured WC films with high adhesion, high hardness, and good toughness suitable for different substrates. This avoids contamination of the chamber by introducing carbon source gases and also avoids the safety hazards associated with using combustible gases and other hazardous gases.

[0027] (2) This invention employs a combination of arc-enhanced glow discharge technology with pre-ionized argon gas and magnetron sputtering of a high-purity WC target. This overcomes the difficulty of generating ionized carbon atoms from a WC compound target (carbon has high ionization energy). Within a high sputtering power range, it achieves high hardness, high adhesion, and low stress deposition of nanostructured WC films with good toughness on the surface of a cemented carbide substrate on small industrial production equipment, with a hardness reaching over 32 GPa. Furthermore, DC magnetron sputtering technology and high-power pulsed magnetron sputtering technology are used to achieve WC... 1-x Controllable preparation of nanocrystalline WC thin films with W2C phase.

[0028] (3) The method of this invention improves upon the shortcomings of conventional methods that involve heating the substrate in a vacuum chamber for an extended period after only one vacuuming, and addresses the adverse effects of trace amounts of volatile impurities and expanding gases. Therefore, the unique operation method of three vacuuming cycles and two temperature changes in this invention effectively avoids the problem of substandard vacuum caused by gas expansion during heating. In addition, by baking the chamber and performing three vacuuming cycles, volatile impurities adsorbed on the inner wall of the chamber and the surface of the substrate are thoroughly removed, ensuring the stability of the vacuum during the subsequent coating deposition process. The second heating temperature is lower than the first heating temperature, which also better ensures the stability of the microstructure of the metal surface. Because our research team found that trace gas expansion has a significant impact on the subsequent formation of highly adhesive nanocrystalline WC films, maintaining the vacuum and cleanliness of the chamber during prolonged heating is crucial. Extensive experiments have demonstrated that the infrared uniform vacuum heating method with three vacuuming cycles and two temperature changes best eliminates interference from volatile impurities, saves operation time, and improves the adhesion of the nanocrystalline WC film.

[0029] (4) This invention employs arc-enhanced glow discharge technology, which generates high-density electrons through arc discharge. Compared with traditional glow discharge technology, the introduction of a high-density electron flow that collides with the introduced argon gas significantly improves its ionization rate. Ion cleaning and etching of the substrate surface have a certain electron heating effect on the substrate and can further remove loose layers, oxides, impurities, etc. on the substrate surface, which is equivalent to "atomic-scale micro-shot peening". Removing impurities from the substrate surface and activating the substrate surface can effectively enhance the bonding performance between the coating and the substrate. The ionized argon ions remaining in the chamber play a pre-ionization role for the reaction gas in subsequent coating, greatly improving the sputtering efficiency during the coating deposition process. Experiments show that the sputtering efficiency is increased by 3-5%. Attached Figure Description

[0030] Figure 1 This is a SEM image of the surface of a cemented carbide substrate.

[0031] Figure 2 This is a SEM image of the surface after etching with arc-enhanced glow discharge technology on cemented carbide.

[0032] Figure 3 Nanocrystalline WC prepared for Example 1 1-x SEM images of the thin film surface.

[0033] Figure 4 The XRD patterns of the nanocrystalline WC thin films prepared in Examples 1, 2, and 3 are shown.

[0034] Figure 5 Nanocrystalline WC prepared for Example 1 1-x OM pattern of thin film scratches.

[0035] Figure 6Nanocrystalline WC prepared for Example 1 1-x SEM images of thin film scratches.

[0036] Figure 7 Nanocrystalline WC prepared for Example 1 1-x OM pattern of the HRA indentation surface of the thin film.

[0037] Figure 8 Nanocrystalline WC prepared for Example 2 1-x SEM images of the thin film surface.

[0038] Figure 9 Nanocrystalline WC prepared for Example 2 1-x OM pattern of thin film scratches.

[0039] Figure 10 Nanocrystalline WC prepared for Example 2 1-x SEM images of thin film scratches.

[0040] Figure 11 Nanocrystalline WC prepared for Example 2 1-x OM pattern of the HRA indentation surface of the thin film.

[0041] Figure 12 SEM image of the surface of the nanocrystalline W2C thin film prepared in Example 3.

[0042] Figure 13 OM pattern of scratches on nanocrystalline W2C thin film prepared in Example 3.

[0043] Figure 14 SEM images of scratches on the nanocrystalline W2C thin film prepared in Example 3.

[0044] Figure 15 OM pattern of HRA indentation surface of nanocrystalline W2C thin film prepared in Example 3. Detailed Implementation

[0045] The specific implementation of the present invention will be further described below with reference to the accompanying drawings and examples, but the present invention is not limited thereto.

[0046] This invention discloses a method for preparing nanocrystalline WC thin films using a magnetron sputtering pure WC compound target. The method is based on a combination of arc-enhanced glow discharge pre-ionized argon gas and a magnetron sputtering high-purity WC target, and includes the following steps:

[0047] 1) Substrate surface pretreatment: After grinding, polishing, cleaning and drying the surface of the substrate to be coated, it is fixed on a planetary table that can rotate in three dimensions and sent into the chamber.

[0048] 2) Chamber vacuum heating: The chamber is evacuated to a vacuum and subjected to multi-stage vacuum heating to remove volatile impurities from the chamber and substrate surface. The heating temperature is set to 550-600℃.

[0049] A uniform infrared vacuum heating method is employed, involving three vacuum cycles and two temperature changes. The second heating temperature is lower than the first; for example, if the first heating temperature is 590℃, the second heating temperature corresponds to 560℃; if the first heating temperature is 580℃, the second heating temperature corresponds to 555℃. This method better ensures the stability of the metal surface microstructure and improves adhesion.

[0050] 3) Ion etching of substrate surface: High-purity argon gas is continuously introduced into the chamber to maintain a constant temperature and pressure in the chamber. A negative bias is applied to the substrate, and arc-enhanced glow discharge technology is used to perform ion cleaning and etching on the substrate to remove the oxide scale and loose layer on the substrate surface.

[0051] The heating temperature of the infrared heating tube in the chamber is 500-600℃, for example, 520℃, 540℃, or 570℃; the argon gas pressure is 0.2-2.0Pa, for example, 0.5Pa, 0.8Pa, 1Pa, or 1.6Pa; the argon gas flow rate is controlled by the gas pressure to 160sccm; and an arc-enhanced glow discharge technology is used to allow a high-density electron flow to collide with the introduced argon gas, and the ion cleaning and etching time of the substrate is 30-60 minutes.

[0052] 4) Preparation of WC thin film: High-purity argon gas is continuously introduced into the chamber. A high-purity WC compound target is used to keep the temperature of the infrared heating tube in the chamber constant. A negative bias voltage is applied to the substrate, and the substrate is treated with magnetron sputtering technology to deposit a nanocrystalline WC thin film.

[0053] 5) Cooling and sampling: After the film deposition is completed, the substrate is cooled to obtain a nanocrystalline WC film on the substrate surface.

[0054] Example 1

[0055] Nanocrystalline WC thin films were prepared on the surface of an ultrafine-grained cemented carbide with a cobalt content of 12 wt.% using the method of this invention, comprising the following steps:

[0056] (1) Surface pretreatment of the substrate: The hard alloy substrate with a roughness Ra value of less than 0.4 μm is ultrasonically cleaned with anhydrous ethanol for 15 min, then dried with hot air, clamped on a planetary carrier that can rotate in three dimensions, and then sent into the processing chamber.

[0057] The chamber is constructed by covering the entire rear wall with infrared electric heating tubes. The temperature inside the chamber is measured by thermocouples located at three positions on the front side of the chamber: upper, middle, and lower. This allows for controlled and uniform heating of the substrate material within the chamber, preventing uneven heating that could create tiny protrusions on the surface and affect the smoothness of subsequent film deposition.

[0058] (2) Chamber evacuation and heating: First, the chamber is evacuated to a vacuum level of 4×10 using a mechanical pump and a molecular pump. -5 Below mbar, the infrared heating tube temperature was then set to 600℃ and the heating time to 30 minutes. After heating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar, the infrared heating tube temperature was then set to 550℃ and the heating time to 30 minutes. After reheating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar.

[0059] Maintaining the vacuum and cleanliness of the chamber is crucial. A uniform infrared vacuum heating method with three vacuuming cycles and two temperature changes is used to thoroughly remove volatile impurities from the chamber and substrate surface, eliminating interference from volatile impurities, saving operation time, and improving the adhesion of the nanocrystalline WC film.

[0060] (3) Ion etching of substrate surface: Before depositing the thin film, the cemented carbide substrate is ion cleaned and etched using arc-enhanced glow discharge technology to enhance the film-substrate bonding ability. The conditions for ion etching are: (i) The arc target acting as the electron source is a Ti target with a purity of over 99% and a target current of 85A; (ii) High-purity argon gas is continuously introduced into the vacuum chamber at a pressure of 1.0Pa, and the argon gas flow rate is controlled by the gas pressure, for example, the argon gas flow rate is controlled by the gas pressure to be 160sccm; (iii) The temperature of the infrared heating tube is set to 500℃; the ion cleaning and etching time is 60min.

[0061] The arc-enhanced glow discharge technology utilizes a high-density electron flow generated by arc discharge, which collides with the introduced argon gas, significantly improving its ionization rate. Ion cleaning and etching of the substrate surface provides a degree of electron heating and further removes loose layers, oxides, and impurities, effectively enhancing the adhesion between the coating and the substrate. The residual ionized argon ions within the chamber pre-ionize the reactive gases for subsequent coating deposition, greatly improving sputtering efficiency during the coating deposition process.

[0062] (4) Deposition of nanocrystalline WC thin film: After ion etching of the substrate surface, high-purity argon gas is continuously introduced into the vacuum chamber at a flow rate of 140 sccm and the temperature of the infrared heating tube is set to 600℃. DC magnetron sputtering technology is used with an average sputtering power of 3kW for the target material and a DC bias voltage of -100V is applied to the substrate for 120 minutes of film deposition.

[0063] Excessive substrate bias voltage can lead to excessive residual stress in the coating, which is not conducive to adhesion to the substrate surface. Insufficient substrate bias voltage is also not conducive to enhancing the cohesion of the coating. To ensure the best coating adhesion, repeated experiments have shown that the substrate bias voltage range of -90 to -110V is better.

[0064] (5) Cooling and sampling: After the coating is completed, the furnace body circulation hot and cold water system is started to cool the chamber. The cooling water temperature is 18℃. The workpiece is cooled to below 70℃ in the vacuum state and can be taken out for storage.

[0065] The hard alloy substrate coated with a nanocrystalline WC thin film obtained by the method in Example 1 was analyzed for multiple properties.

[0066] 1. Morphological characteristics: Figure 1 , Figure 2 and Figure 3 The SEM images show the surface morphology of the cemented carbide substrate, the substrate after ion etching, and the nanocrystalline WC thin film, respectively. Figure 3 In the study, the nanocrystalline WC thin film deposited by DC magnetron sputtering technology exhibits a "cauliflower-like" morphology on its surface, with no obvious defects such as droplets or voids, and the nanocrystalline WC thin film is uniform and dense.

[0067] Compared Figure 1 In the middle, the surface of the uncoated cemented carbide substrate has a small number of scratches and other machining marks.

[0068] 2. Hardness Characterization: The nanoscale hardness and elastic modulus of the thin film samples were characterized using a nanoindentation instrument. The hardness of the nanocrystalline WC thin film was 35.603 GPa, and the elastic modulus was 491.702 GPa. The hardness of the cemented carbide substrate was 16.484 GPa, indicating that preparing a nanocrystalline WC thin film on the surface of the cemented carbide substrate can effectively improve its surface hardness.

[0069] 3. Phase Characterization: The phase structure of the nanocrystalline WC thin film prepared by the method in Example 1 is shown in [reference needed]. Figure 4 It can be seen that the phase structure of the nanocrystalline WC thin film is mainly cubic WC. 1-x The phase exhibits a distinct (200) preferred orientation. The diffraction peaks of the WC thin film show significant broadening, which is caused by the grain refinement of the nanocrystalline WC thin film. The grain refinement gives the nanocrystalline WC thin film higher hardness.

[0070] 4. Characterization of membrane-substrate adhesion: The membrane-substrate adhesion was characterized using the scratch method. At a loading rate of 50 N / min, the loading load ranged from 0 to 100 N, and the scratch length was 5 mm. Figure 5 The scratch morphology of nanocrystalline WC thin film on cemented carbide. Figure 6 This shows the scratch morphology under high load at the end of the scratching process. The critical failure load L of the nanocrystalline WC thin film is visible. c2 It is approximately 86N, and the membrane substrate has good bonding. Figure 7 The image shows the HRA indentation morphology of a nanocrystalline WC thin film on a cemented carbide substrate. The film and the substrate undergo synergistic deformation with no obvious signs of peeling. A small number of radial cracks are observed. The adhesion strength can be rated as HF 1, indicating good film-substrate bonding.

[0071] Example 2

[0072] Nanocrystalline WC thin films were prepared on the surface of an ultrafine-grained cemented carbide with a cobalt content of 12 wt.% using the method of this invention, comprising the following steps:

[0073] (1) Surface pretreatment of the substrate: The hard alloy substrate with a roughness Ra value of less than 0.4 μm is ultrasonically cleaned with anhydrous ethanol for 20 min, then dried with hot air, clamped on a three-dimensional rotatable planetary carrier, and then sent into the chamber.

[0074] (2) Vacuuming of the chamber: First, the chamber is evacuated to a vacuum level of 4×10 using a mechanical pump and a molecular pump. -5 Below mbar, the infrared heating tube temperature was then set to 600℃ and the heating time to 30 minutes. After heating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar, the infrared heating tube temperature was then set to 550℃ and the heating time to 30 minutes. After reheating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar, volatile impurities on the chamber and substrate surface are thoroughly removed.

[0075] (3) Ion etching of substrate surface: Before depositing the thin film, the cemented carbide substrate is ion cleaned and etched using arc-enhanced glow discharge technology to enhance the film-substrate bonding ability. The conditions for ion etching are: (1) The arc target used as the electron source is a Ti target with a purity of over 99% and a target current of 87A; (2) High-purity argon gas is continuously introduced into the vacuum chamber at a pressure of 1.5Pa, and the Ar flow rate is controlled by the gas pressure; (3) The temperature of the infrared heating tube is set to 500℃; the ion cleaning and etching time is 70min.

[0076] (4) Deposition of nanocrystalline WC thin film: After ion etching of the substrate surface, high-purity argon gas is continuously introduced into the vacuum chamber at a flow rate of 140 sccm and the temperature of the infrared heating tube is set to 600℃. DC magnetron sputtering technology is used with an average sputtering power of 4kW for the target material. A DC bias voltage of -100V is applied to the sample for 120 min of film deposition.

[0077] (5) Cooling and sampling: After the coating is completed, the furnace body circulation hot and cold water system is started to cool the chamber. The cooling water temperature is 18°C. The workpiece is cooled to below 70°C in the vacuum state and then taken out and stored in a constant temperature drying oven.

[0078] The hard alloy substrate coated with nanocrystalline WC thin film obtained by the method in Example 2 was analyzed for multiple properties.

[0079] 1. Morphological characteristics: Figure 8 The surface SEM morphology of the nanocrystalline WC thin film prepared in Example 2 of this invention is shown. Figure 8 The surface of the nanocrystalline WC film exhibits a "cauliflower-like" morphology, with no obvious defects such as droplets or voids, and the nanocrystalline WC film is uniform and dense.

[0080] 2. Hardness Characterization: The nanoscale hardness and elastic modulus of the thin film samples were characterized using a nanoindentation instrument. The hardness of the nanocrystalline WC thin film was 32.273 GPa, and the elastic modulus was 471.595 GPa. The hardness of the cemented carbide substrate was 16.484 GPa. By comparison, it can be seen that preparing a nanocrystalline WC thin film on the surface of the cemented carbide substrate can effectively improve its surface hardness.

[0081] 3. Phase characterization: See Figure 4 The phase structure of nanocrystalline WC thin films is mainly cubic WC. 1-x The phase exhibits a distinct (200) preferred orientation. This is due to the grain refinement of the nanocrystalline WC film, which gives the nanocrystalline WC film higher hardness.

[0082] 4. Characterization of membrane-substrate adhesion: The membrane-substrate adhesion was characterized using the scratch method. At a loading rate of 50 N / min, the loading load ranged from 0 to 100 N, and the scratch length was 5 mm. Figure 9 The scratch morphology of nanocrystalline WC thin film on cemented carbide. Figure 10 The scratch morphology under high load at the end of the scratching process shows the critical failure load L of the nanocrystalline WC thin film. c2 Approximately 66N, with good membrane-substrate bonding; Figure 11 The image shows the HRA indentation morphology of a nanocrystalline WC thin film on a cemented carbide substrate. The film and the substrate undergo synergistic deformation with no obvious signs of peeling. A small number of radial cracks are observed. The adhesion strength can be rated as HF 1, indicating good film-substrate bonding.

[0083] Example 3

[0084] Nanocrystalline WC thin films were deposited on the surface of an ultrafine-grained cemented carbide with a cobalt content of 12 wt.% by high-power pulsed magnetron sputtering, including the following steps:

[0085] (1) Surface pretreatment of the substrate: The hard alloy substrate with a roughness Ra value of less than 0.4 μm is ultrasonically cleaned with anhydrous ethanol for 15 min, then dried with hot air, clamped on a three-dimensional rotatable planetary carrier, and then sent into the chamber.

[0086] (2) Vacuuming of the chamber: First, the chamber is evacuated to a vacuum level of 4×10 using a mechanical pump and a molecular pump. -5 Below mbar, the infrared heating tube temperature was then set to 600℃ and the heating time to 30 minutes. After heating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar, the infrared heating tube temperature was then set to 550℃ and the heating time to 30 minutes. After reheating, the chamber vacuum was evacuated to 4×10⁻⁶ mbar. -5 Below mbar, volatile impurities on the chamber and substrate surface are thoroughly removed.

[0087] (3) Ion etching of substrate surface: Before depositing the thin film, the cemented carbide substrate is ion cleaned and etched using arc-enhanced glow discharge technology to enhance the film-substrate bonding ability. The conditions for ion etching are: (1) The arc target used as the electron source is a Ti target with a purity of over 99% and a target current of 76A; (2) High-purity argon gas is continuously introduced into the vacuum chamber at a pressure of 1.6Pa, and the argon gas flow rate is controlled by the gas pressure; (3) The temperature of the infrared heating tube is set to 500℃; the ion cleaning and etching time is 70min.

[0088] (4) Deposition of nanocrystalline WC thin film: After ion etching of the substrate surface, high-purity argon gas is continuously introduced into the vacuum chamber at a flow rate of 140 sccm and the temperature of the infrared heating tube is set to 600℃. High-power pulsed magnetron sputtering technology is used, with an average sputtering power of 3kW for the target material, a pulse on-time of 40μs / 1000μs, and a DC bias voltage of -100V applied to the sample for 180min of film deposition.

[0089] (5) Cooling and sampling: After the coating is completed, the furnace body circulation hot and cold water system is started to cool the chamber. The cooling water temperature is 18℃. The workpiece is cooled to below 70℃ in the vacuum state and then taken out and stored in a constant temperature drying oven.

[0090] The hard alloy substrate coated with nanocrystalline WC thin film obtained by the method in Example 3 was analyzed for multiple properties.

[0091] 1. Morphological characteristics: Figure 12 Nanocrystalline WC films deposited by high-power pulsed magnetron sputtering exhibit no obvious characteristic morphology, displaying clear WC grain outlines on a cemented carbide substrate. The films are uniform and dense, free of significant droplets, voids, or other defects. Compared to… Figure 1 In the middle, the surface of the uncoated cemented carbide substrate has a small number of scratches and other machining marks.

[0092] 2. Hardness Characterization: The nanoscale hardness and elastic modulus of the thin film samples were characterized using a nanoindentation instrument. The hardness of the nanocrystalline WC thin film was 35.122 GPa, and the elastic modulus was 513.393 GPa. The hardness of the cemented carbide substrate was 16.484 GPa. Preparing a nanocrystalline WC thin film on the surface of the cemented carbide substrate can effectively improve its surface hardness.

[0093] 3. Phase characterization: See Figure 4 The phase structure of nanocrystalline WC films is mainly cubic W2C phase, which is caused by the grain refinement of nanocrystalline WC films. The grain refinement makes nanocrystalline WC films have high hardness.

[0094] 4. Characterization of membrane-substrate adhesion: The membrane-substrate adhesion was characterized using the scratch method. At a loading rate of 50 N / min, the loading load ranged from 0 to 100 N, and the scratch length was 5 mm. Figure 13 The scratch morphology of nanocrystalline WC thin film on cemented carbide. Figure 14 The scratch morphology under high load at the end of the scratching process shows that when the indenter load is applied to 100N, the film does not show obvious signs of peeling and undergoes coordinated deformation with the substrate, indicating good film-substrate bonding. Figure 15 The image shows the HRA indentation morphology of a nanocrystalline WC thin film on a cemented carbide substrate. The film and the substrate undergo synergistic deformation with no obvious signs of peeling. A small number of radial cracks are observed. The adhesion strength can be rated as HF 1, indicating good film-substrate bonding.

[0095] The preparation method of this invention is controllable and can obtain nanocrystalline WC thin films with high hardness, high adhesion, and low stress on the surface of cemented carbide substrates, showing good application prospects. Specifically, it employs a combination of arc-enhanced glow discharge technology with argon pre-ionization and magnetron sputtering of a high-purity WC target. Several key preparation parameters are carefully controlled to achieve technological fusion. Within a higher sputtering power range, DC magnetron sputtering or high-power pulsed magnetron sputtering technology is used to achieve the deposition of high-hardness, high-adhesion, and low-stress nanocrystalline WC thin films on the surface of cemented carbide substrates.

Claims

1. A method for preparing nanocrystalline WC thin films by magnetron sputtering of pure WC compound targets, characterized in that: The combined technology based on arc-enhanced glow discharge pre-ionized argon gas and magnetron sputtering of a high-purity WC target includes the following steps: 1) Substrate surface pretreatment: After grinding, polishing, cleaning and drying the surface of the substrate to be coated, it is fixed on a planetary table that can rotate in three dimensions and sent into the chamber. 2) Chamber vacuum heating: First, the chamber is evacuated to a vacuum level of 4×10⁻⁶. -5 Below mbar, followed by the first heating, and then the chamber vacuum was evacuated to 4×10. -5 Below mbar, a second heating process is performed, with the second heating temperature lower than the first heating temperature, ultimately evacuating the chamber to a vacuum level of 4 × 10⁻⁶ mbar. -5 Below mbar, remove easily volatile impurities from the chamber and substrate surface, and set the heating temperature to 550-600°C; 3) Ion etching of the substrate surface: High-purity argon gas is continuously introduced into the chamber to maintain a constant temperature and pressure. A negative bias is applied to the substrate, and arc-enhanced glow discharge technology is used to perform ion cleaning and etching on the substrate surface to remove the oxide scale and loose layer. During the ion cleaning and etching process, the cathode arc target acting as the electron source is a Ti target with a purity of over 99%, and the target current is 70-90A. The planetary carrier holding the substrate is connected to the negative terminal of the pulse power supply, and the negative bias is... 50~ 200V, using bipolar pulse, frequency of 15-20kHz, duty cycle of 60-80%; 4) Preparation of WC thin film: High-purity argon gas is continuously introduced into the chamber. A high-purity WC compound target is used, and the temperature of the infrared heating tube in the chamber is kept constant. A negative bias voltage is applied to the substrate, and a nanocrystalline WC thin film is deposited on the substrate using magnetron sputtering technology. When DC magnetron sputtering technology is used, the average sputtering power of the target is 3kW to 4kW. The planetary carrier holding the substrate is connected to the negative terminal of the power supply, and the negative bias voltage is... 90~ 110V, thin film deposition time is 100–120 min; when using high-power pulsed magnetron sputtering technology, the average sputtering power of the target is 3kW, and the pulse duty cycle is 0.5%–5%; the planetary carrier holding the substrate is connected to the negative terminal of the power supply, and the negative bias voltage is... 90~ 110V, thin film deposition time is 160-180 min; 5) Cooling and sampling: After the deposition of the film is completed, the substrate is cooled to obtain a nanocrystalline WC film on the substrate surface. The hardness of the nanocrystalline WC film is ≥32GPa.

2. The method according to claim 1, characterized in that: The surface roughness Ra value of the substrate mentioned in step 1) is below 0.4 μm; ultrasonic cleaning is performed by ultrasonically cleaning the substrate with anhydrous ethanol for 10 to 20 minutes, and then drying it with hot air.

3. The method according to claim 1, characterized in that: The chamber is constructed by covering the entire rear wall with infrared heating tubes. The temperature inside the chamber is measured by thermocouples located at the top, middle, and bottom of the front side of the chamber.

4. The method according to claim 1, characterized in that: In step 3), the infrared heating tube is heated to 500-600°C, the argon gas pressure is 0.2-2.0 Pa, and the arc-enhanced glow discharge technology is used to allow the high-density electron flow to collide with the introduced argon gas. The ion cleaning and etching time of the substrate is 30-60 min.

5. The method according to claim 1, characterized in that: In step 4), a rectangular WC compound target with a purity of 99.9% is used as the sputtering target.

6. A nanocrystalline WC thin film on a metal substrate, characterized in that: It is prepared by the method described in any one of claims 1-5.

Citation Information

Patent Citations

  • Method of depositing W-N hard membrane on surface of hard alloy through direct-current magnetron sputtering

    CN107267916A

  • Catalysis electrode of tungsten carbide

    CN1727883A